PENGARUH TINGKAT KESEHATAN BANK SYARIAH DAN MAQASYID SYARIAH INDEKS TERHADAP PERTUMBUHAN LABA DENGAN GOOD CORPORATE GOVERNANCE SEBAGAI VARIABEL MODERATING - YUSUF FAISAL (Al-Masraf: Jurnal Lembaga Keuangan dan Perbankan, 2018)
The purpose of this study is to see the effect of bank health, Sharia Maqasyid Index on the profit growth of Islamic banks in Indonesia in 2011 - 2017 with Good Corporate Governance as a moderating variable. By using secondary data from Islamic bank financial statements and good corporate governance reports from 2011-2018. Analysis tools use Moderated Regression Analysis (MRA). Based on the results of the study that the NPF variable has an insignificant effect on earnings growth. The results showed that the FDR variable had an insignificant effect on earnings growth. Thus this study rejects the second hypothesis which states that FDR has a significant effect on earnings growth. This is evidenced by the results of hypothesis testing with a probability value greater than 5% significance value (0.578> 0.05). ROA variable has a significant effect on profit growth. Thus this study accepts the third hypothesis which states that ROA has a significant effect on profit growth. This is evidenced by the results of hypothesis testing with a probability value smaller than the 5% significance value (0.000 <0.05). It is known that the NIM variable has a significance of 0.874 greater than 0.05 in other words that the NIM variable partially has no effect on profit growth. CAR variable has no effect on profit growth obtained a significance value> 0.05, which is 0.360. Regression coefficients for Shariah Maqasyid Index (MSI) are 6,422 and positive sign, which means if the MSI variable experiences a 1% increase, then profit growth will increase by 6,422. Coefficient is positive means that there is a positive relationship between MSI and profit growth, the higher the MSI ratio conducted by the company, the higher the company's profit growth.